2022
DOI: 10.1094/pdis-09-21-2069-re
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Endophytic Bacterial Microbiota of Asymptomatic and Symptomatic Ginger Rhizomes During the Activation of Adventitious Bud Development

Abstract: Bacterial infections are the cause of rhizome rot in ginger (Zingiber officinale). Key members of the endophytic microbial community in ginger rhizomes have not been identified and their impact on the decay of rhizomes during the activation of adventitious bud development has not been investigated. High-throughput, 16S rRNA amplicon sequencing and inoculation experiments were used to analyze the microbial diversity, community structure and composition, and the pathogenicity of isolated bacteria. Our results in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…The fungal flora was more diverse in ND samples than in asymptomatic fruit samples. This finding is similar to the results in our previous that found that during the process of decay development in ginger, the diversity of bacterial communities increased in symptomatic samples (Huang et al, 2022 ). The ability of the four newly identified pathogens to infect mature kiwifruit was also investigated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The fungal flora was more diverse in ND samples than in asymptomatic fruit samples. This finding is similar to the results in our previous that found that during the process of decay development in ginger, the diversity of bacterial communities increased in symptomatic samples (Huang et al, 2022 ). The ability of the four newly identified pathogens to infect mature kiwifruit was also investigated.…”
Section: Discussionsupporting
confidence: 93%
“…The interaction between a host and its endophytic microbial community is also affected by biological or environmental factors (Brader et al, 2017 ). Our previous study demonstrated that different environmental conditions can result in a shift in the structure of the endophytic microbial community of kiwifruit that either prevents (Sui et al, 2021 ) or promotes disease (Huang et al, 2022 ). The introduction of fungal pathogens through natural or artificial (inoculation) means could greatly increase the potential for a shift in the endophytic fungal community of fruit (Yin et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Less is known about the relevance of Streptococcaceae to plant growth. In Zingiber officinale , this family was significantly enriched in rhizomes with advanced stages of soft rot (Huang et al 2022). However, Streptococcaceae is prevalent in soil and plants (Chuah et al 2016; Wang et al 2021), typically at higher abundance in aerial plant compartments than in the rhizosphere (Minervini et al 2015; Yu et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Less is known about the relevance of Streptococcaceae to plant growth. In Zingiber officinale, this family was significantly enriched in rhizomes with advanced stages of soft rot (Huang et al 2022).…”
Section: Microbial Taxa Associated With Plant Growthmentioning
confidence: 99%